2003
DOI: 10.1007/s00438-003-0938-8
|View full text |Cite
|
Sign up to set email alerts
|

Two-hybrid search for proteins that interact with Sad1 and Kms1, two membrane-bound components of the spindle pole body in fission yeast

Abstract: In interphase cells of fission yeast, the spindle pole body (SPB) is thought to be connected with chromosomal centromeres by an as yet unknown mechanism that spans the nuclear membrane. To elucidate this mechanism, we performed two-hybrid screens for proteins that interact with Kms1 and Sad1, which are constitutive membrane-bound components of the SPB that interact with each other. Seven and 26 genes were identified whose products potentially interact with Kms1 and Sad1, respectively. With the exception of Dlc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 73 publications
3
93
0
Order By: Relevance
“…Preliminary mass spectrometric analysis of a Ppc89 purification indicates that several coil-coil proteins including Pcp1 (Flory et al, 2002), Kms2 (Miki et al, 2004), and Cut12 (Bridge et al, 1998) copurify (unpublished observation). These are strong candidates for additional direct binding partners and studies are underway to test this possibility.…”
Section: Ppc89 and Spb Structurementioning
confidence: 97%
See 2 more Smart Citations
“…Preliminary mass spectrometric analysis of a Ppc89 purification indicates that several coil-coil proteins including Pcp1 (Flory et al, 2002), Kms2 (Miki et al, 2004), and Cut12 (Bridge et al, 1998) copurify (unpublished observation). These are strong candidates for additional direct binding partners and studies are underway to test this possibility.…”
Section: Ppc89 and Spb Structurementioning
confidence: 97%
“…Sad1 contains one transmembrane helix domain and is required for mitotic functions of the SPB (Hagan and Yanagida, 1995). Interacting with Sad1 are Kms1 and Kms2, which contain coil-coiled and transmembrane helices and are not essential for vegetative growth (Niwa et al, 2000;Miki et al, 2004). Kms1 is essential for telomere clustering and SPB function during meiosis (Shimanuki et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). 4,12,13 In the kms1 can provide Sad1 with additional attachment sites on the nuclear envelope where telomeres locate. Indeed, multiple Sad1 foci can be seen on the nuclear envelope in addition to the SPB during the process of telomere clustering in meiotic prophase.…”
Section: Bouquet Formation Of Chromosomes In Meiotic Prophasementioning
confidence: 99%
“…1b). [34][35][36][37] This results in telomere clustering and later in nuclear oscillation between the cell poles, which facilitates homologous paring and recombination. 38 In mammals, a recent study revealed the formation of a Unknown MSP-300 D-Titin/Sallimus: anchoring mitochondria and endoplasmic reticulum to the striated muscle Z-discs.…”
Section: Nuclear Positioning In Plantsmentioning
confidence: 99%